Local area network simulation program - Goh, Beng Huat (University Malaysia Sarawak (UNIMAS), 2000)
This paper presents a program used in the simulation of a Local Area Network (LAN), which is written in Visual Basic 6.0 and runs in Windows 98 Operating System. The main objective would be to analyze the performance of a LAN using simulation and introduce some basic understanding of the functionality and how various types of LAN work.